(3TQM OjhGf GdMSf Hf CSO GdaGQbis - (3CHh fUQ GdMSf Hf GSO Hf GdMSf GdaGQbi,J (B487 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hHYO agPg GdGHjGJ GdJi CfTOgG GdTjN GdGeGe GHh fUQ GdMSf GdaGQbi MQa GdCda cja fQei Ydi GdaQGT hde GTed GdTGe s
(3BNQgG (B:s
(3MQa GdjGA aLGd Ydi hMTjI hJNGdg Ydi eJfg SHG MOjO GjeGfkG gPG BNQ GdGHjGJ GdJi CfTOgG ai edNU GdGjVGM hPcQ EYQGHgG s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B206s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs